Principles of Geology and sensory experience at London's Cyclorama - Hibberd, Sarah (University of California Press, 2015)
The Cyclorama opened in London in 1848 with a representation of the 1755 Lisbon earthquake that reportedly terrified audiences with its realistic aural and visual effects. During the first half of the century Londoners had been confronted with a rapid succession of revolutions in scientific thought, which needed to be assimilated into the emotional as well as the intellectual structures of public life. The geologist Charles Lyell had recently explained earthquakes and volcanic activity in a manner that fundamentally changed public understanding of the history of the earth, and in so doing challenged the religious narratives that had formerly underpinnedit. The Cyclorama invited the spectator to confront such destruction in this new light: the frighteningly immersive visual and aural effects and the comforting narratives offered by accompanying musical excerpts (from works by Auber, Beethoven, and Rossini) were crucial to the shaping of the experience, and can be understood in the context of other artistic and poetic responses to Lyell’s proposals. The music helped to articulate something of the competing perspectives on the crisis of faith that was exercising the intelligentsia at mid-century and offered a conduit for both emotional and intellectual responses.